2014
DOI: 10.1002/we.1754
|View full text |Cite
|
Sign up to set email alerts
|

A Tomo‐PIV study of the effects of freestream turbulence on stall delay of the blade of a horizontal‐axis wind turbine

Abstract: Volumetric velocity fields were measured using tomographic particle image velocimetry on a model of the blade of a 5 kW horizontal‐axis wind turbine to study the effects of freestream turbulence levels (FTLs) at 0.4%, 4% and 13% on stall delay phenomenon at two different global tip speed ratios of 3 and 5 with Reynolds number (Re) ࣈ 5000. Static pressures were measured, and results illustrated that FTL has stronger effect on the surface pressures of the static airfoil. Magnitudes of the absolute velocities wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…The iso-contours represent the vorticity. There is a large vortex behind the rotating blade and the flow started to partially separate, which is different with the case for the static airfoil at the AOA of 30 degrees [14,16] where the flow is fully separated; while the flow at TSR=5 is still attached, which is the same as the previous results [14] . Note that a strong reversed flow from the trailing edge to leading edge at near the suction surface of the blade at a higher Reynolds number (Re = 8683) has been observed at TSR=3, which perhaps shows the Reynolds number effects on the stall delay.…”
Section: Time-resolved Piv Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The iso-contours represent the vorticity. There is a large vortex behind the rotating blade and the flow started to partially separate, which is different with the case for the static airfoil at the AOA of 30 degrees [14,16] where the flow is fully separated; while the flow at TSR=5 is still attached, which is the same as the previous results [14] . Note that a strong reversed flow from the trailing edge to leading edge at near the suction surface of the blade at a higher Reynolds number (Re = 8683) has been observed at TSR=3, which perhaps shows the Reynolds number effects on the stall delay.…”
Section: Time-resolved Piv Resultscontrasting
confidence: 73%
“…They, for the first time, measured the detailed threedimensional and volumetric velocity fields using Tomographic PIV on a model of the rotating blade of a small-scale HAWT to study the physics of stall delay at two different global tip speed ratios (TSRs) [The tip-speed ratio or TSR for wind turbines is the ratio between the tangential speed of the tip of a blade and the actual speed of the wind.] at about Re=5000 [14][15][16][17][18] . Their results showed that rather than the recirculation separation bubbles with strong reversed flows for the static airfoil at deep stall, the attached flows were observed on the suction surface of the rotating blade [14,15,17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further validation of our numerical results has been planned to use state-of-the-art three-dimensional PIV measurements [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties arise, however, when the rotor operates in an unsteady state. The unsteady-flow condition leads to cyclic turbine operation [32], dynamic stall [33], aerodynamic effects [34] and overall reduction of power in wind turbines [35], whereas in tidal stream turbines, its effects are little understood. In recent years, various scaled turbines are being studied in test laboratories comprising different flow conditions: current with low and high turbulence alone, and current combined with waves [36].…”
Section: B Turbine Operationmentioning
confidence: 99%